Healing after COVID-19: are survivors at risk for pulmonary fibrosis? - McDonald, Lindsay T. (American journal of physiology. Lung cellular and molecular physiology, 2021)
The novel SARS-CoV-2 coronavirus, which is responsible for COVID-19 disease, was first reported in Wuhan, China, in December of 2019. The virus rapidly spread, and the World Health Organization declared a pandemic by March 2020. With millions of confirmed cases worldwide, there is growing concern and considerable debate regarding the potential for coronavirus infection to contribute to an appreciable burden of chronic respiratory symptoms or fibrotic disease among recovered individuals. Because the first case of COVID-19 was documented less than one year ago, data regarding long-term clinical outcomes are not yet available, and predictions for long-term outcome are speculative at best. However, due to the staggering number of cases and the severity of disease in many individuals, there is a critical need to consider the potential long-term implications of COVID-19. This review examines current basic and clinical data regarding fibrogenic mechanisms of viral injury in the context of SARS-CoV-2. Several intersecting mechanisms between coronavirus infection and fibrotic pathways are discussed to highlight factors and processes that may be targetable to improve patient outcome. Reports of post-infection sequelae from previous coronavirus outbreaks are presented toward the goal of improved recognition of potential contributing risk factors for fibrotic disease.